EXPANSÃO DO ENSINO SUPERIOR FEDERAL E DESENVOLVIMENTO REGIONAL: O CASO DA UNIVERSIDADE FEDERAL DO PARANÁ NO LITORAL PARANAENSE - Clovis Wanzinack (Universidade Federal de Santa Catarina, 2014)
This study aims to describe and reflect about some of the approaches adopted by a university campus, created with a purpose to identifying vulnerabilities and minimizing problems of its surroundings, contributing to regional development. With recent Brazilian National Policy for expanding the Federal Higher Education Network, it was created the Coastal Campus of the Universidade Federal do Paraná (UFPR Litoral) in Matinhos, coast of Paraná´s State. For this study, it was conducted theoretical and social qualitative research, through document analysis and conducting semi-structured interviews with social actors (managers, professors and coordinators) who are experiencing historically the deployment process of this campus. Research identified: regional patrimonies and vulnerabilities, justifying the viability of the campus at this location; conceptions of Regional Development related to sustainability and eco-development which are institutionally adopted; student´s graduation through a different methodological approach, which aims to instrumentalize them to intervene in regional context, through specific approaches. The consolidation of this study allowed us to understand some of the processes about UFPR Litoral, raising some questions about the ways in which it proposes to contribute to regional development and some features of an ongoing proposal, which requires the continuation of studies and research.